The Impact Of Management Information Systems On The Training Of Workers In The Directorate Of Education Salah Al-Din (Case Study) - Abdullah, Mohammed Faraj (Journal of Technology and System Information, 2025)
The aim of this study is to find a possible relationship between the management information system and the training of workers in the General Directorate of Education in Salah al-Din. This work was established on the basis of taking random samples of workers who are considered critical elements. The researcher raised some questions that are directly related to the main statement. The comparative description system was adapted to obtain the results using a questionnaire form where all the data were collected from GEDS. Many theories were tested and 205 forms were distributed and five of them were defective and only 200 forms were analyzed. The study found that there is a relationship between the positive attitudes of the management information system and workers in training. The study recommends the need to provide a clear system for evaluating the performance index for workers. In addition, training should follow an open policy to help workers solve their problems. In particular. It is necessary to have direct communication with the direct manager to address the obstacles facing his performance.